The House, the Table, and the Message: Spatial Dynamics in the Synoptic Gospels - Glaser, Timo (Journal for the study of the New Testament, 2026)
This study explores spatial dynamics in the synoptic Gospels, focusing on how each synoptic Gospel author frames Jesus's movements and the significance of "the house", with particular attention to table fellowship with Levi as a narrative marker. While Luke depicts Jesus as a wandering teacher, Matthew anchors him in Capernaum, portraying his own house as a hub for ministry. Mark takes a middle approach, linking Jesus to the house of Simon and Andrew. Through both close and distant reading, this article examines how spatial language shapes theological perspectives on early Christian community structures and reveals the distinct narrative strategies that define each Gospel's portrayal of Jesus.